2016
DOI: 10.1111/cas.12934
|View full text |Cite
|
Sign up to set email alerts
|

Y‐632 inhibits heat shock protein 90 (Hsp90) function by disrupting the interaction between Hsp90 and Hsp70/Hsp90 organizing protein, and exerts antitumor activity in vitro and in vivo

Abstract: Heat shock protein 90 (Hsp90) stabilizes a variety of proteins required for cancer cell survival and has been identified as a promising drug target for cancer treatment. To date, several Hsp90 inhibitors have entered into clinical trials, but none has been approved for cancer therapy yet. Thus, exploring new Hsp90 inhibitors with novel mechanisms of action is urgent. In the present study, we show that Y‐632, a novel pyrimidine derivative, inhibited Hsp90 in a different way from the conventional Hsp90 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…For signaling protein expression changes, we found that Hsp70 was induced in all four cell lines, which is a canonical effect of this class of Hsp90 inhibitors and serves as a marker of Hsp90 inhibition (Fig. 1, A and B) (24,25). We also found that Hsp90 inhibition altered the protein expression levels of the MOR itself and of the signaling regulator ␤arr2 and the kinase Akt.…”
Section: Hsp90 Inhibition In Cell Models Of Mor Signalingmentioning
confidence: 63%
“…For signaling protein expression changes, we found that Hsp70 was induced in all four cell lines, which is a canonical effect of this class of Hsp90 inhibitors and serves as a marker of Hsp90 inhibition (Fig. 1, A and B) (24,25). We also found that Hsp90 inhibition altered the protein expression levels of the MOR itself and of the signaling regulator ␤arr2 and the kinase Akt.…”
Section: Hsp90 Inhibition In Cell Models Of Mor Signalingmentioning
confidence: 63%
“…Western blotting was carried out as described previously . In brief, cells were lysed in SDS sample buffer, then separated by SDS‐PAGE, and transferred to PVDF membranes (Millipore, Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was carried out as described previously. (16) In brief, cells were lysed in SDS sample buffer, then separated by SDS-PAGE, and transferred to PVDF membranes (Millipore, Bedford, MA, USA). Membranes were incubated with primary antibodies at 4°C overnight and then with secondary antibodies for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these toxoflavins are compromised in their usefulness by being ubiquitous ‘frequent hitters’ in HTS campaigns as well as very toxic to cells 40 43 . More recently, a structurally related chemical series of thiol-reactive acrylamide-containing compounds has also been published 44 . These compounds do not bind Hsp90 or its cochaperones, but exert their activity through intracellular thiol oxidation.…”
Section: Introductionmentioning
confidence: 99%